Identification and ranking of critical success practices for projects and products - Ketkale, Harshwardhan, author; Batchelor, Ann, advisor; Adams, James, committee member; Albert, Lumina, committee member (Colorado State University. Libraries, 2020)
Project results continue to fail despite the large number of efforts invested by researchers towards project success (Terry Cooke Davies, 2002). Identification of Critical Success Factors for a product/project has been a challenge (Uluocak, 2013). Thus, it is essential to conduct study in determining these primary factors contributing towards product/project success. Although several studies have been conducted in identifying the success factors for product/project in diverse range of areas but none have explored actual industrial scenarios from a wide range of fields to derive the critical success practices followed by validation through working professionals. Thus, this study aimed at identifying the critical success practices for projects/products. The research design constituted of in-depth case studies allowing an outlook into actual industrial scenarios providing a list of critical practices contributing towards success as well as failure of a product/project in various fields as the first part. Second part of the research involved validation of the determined critical practices through focus-group survey with working professionals and graduate students. This study data exhibited variation in the views of survey subjects towards the critical success practices based on their work experience, possession of INCOSE/PMI certification and in terms of their roles in the firm such as Managers, Engineers, Marketing/Sales, and Engineering managers. RII tool and Henry Garrett Ranking Method were used to analyze data from Likert-scale based and ranking questions respectively/ In conclusion, this study was also able to identify, evaluate and rank the critical success practices for a wide range of projects/products providing a foundation for execution of successful projects in future.
Keywords: Henry Garrett ranking method; project/product success; critical success practices; relative importance index; project case studies